The impact of the national economic recovery program and digitalization on MSME resilience during the COVID-19 pandemic: A case study of Bank Rakyat Indonesia - Supari Supari; Hendranata Anton (Economies, 2022)
This study aims to evaluate the impact of the National Economic Recovery Program-Pemulihan Ekonomi Nasional (PEN) and digitalization on micro, small, and medium enterprises' (MSMEs) resilience during the COVID-19 pandemic. This research is based on primary data from a survey of 6009 Bank Rakyat Indonesia customers conducted from March-June 2021. Using the generalized ordered logistic regression technique, this study found that a combination of new loans, credit restructuring, and/or interest subsidies was the most successful PEN for enhancing MSME resilience. Meanwhile, providing new loans merely improved liquidity, not sales or profitability. However, just providing a restructuring program weakened resiliency. This research also discovered that MSMEs that have been digitalizing for more than a year are more resilient than those that have not. This study highlights the necessity of offering several interventions for MSMEs and assisting MSMEs in going digital to improve MSME resilience during the COVID-19 pandemic.
Keywords: 330; BRI; digitalization; government support; MSME resilience; PEN